Analyzing Polarization on Social Media: A Case Study of the 2022 Brazil Presidential Election - Costa, Felipe Soares (2023)
Project Work presented as the partial requirement for obtaining a Master's degree in Data Science and Advanced Analytics, specialization in Data Science